The Role of Government in Disaster Risk Reduction (DRR) in the Coastal Areas of Bangladesh - Kabir, Md. Alaul (International Journal of Computer Sciences and Engineering, 2022)
Bangladesh locates in disaster prone area in South Asia because of its geographical location. Various types of disasters like flood, cyclone, river-bank erosions, drought, salinity etc. are the common phenomenon in this land. Such natural disaster left huge people died or wounded and destroying valuable wealth’s around the year. In the recent time, natural calamities have increased remarkably. This study follows qualitative research methodology and reveals that the people living in coastal areas are facing severe natural hazard that badly impact on their lifestyle. The study found that the government has been conducting various risk reduction programmes like prewarning signals, disbursing posters and leaflets, conducing knowledge sharing meeting, awareness rising training to mitigate the losses. Besides, some nongovernment organizations also have been playing vital role to face this calamity. This study also has drawn a conclusion with recommendations that will leave the scope to take effective action in this circumstance.